Domain wall dynamics in engineered multilayer magnetic nanostructures - Lin, Eddy Junxiang (Nanyang Technological University, 2014)
Magnetic domain walls is the cornerstone for novel non-volatile storage and logic devices. These devices offer innumerable advantages such as low power consumption and high integration densities. The realisation of domain wall based devices requires better understanding of the domain wall structure and dynamics. The ability to manipulate and control high speed domain wall in nanowire networks is crucial.